Διερεύνηση του επιπέδου υγείας των μητέρων μονογονεϊκών οικογενειών στην Κύπρο - Ρούσου, Έλενα (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Background: The number of single-parent families is rapidly growing worldwide. The majority is being headed by mothers. A large part of the international literature reveals that single motherhood is associated with increased levels of chronic stress, mainly due to economic distress and reduced levels of social support, which may eventually lead to physical and psychological illness. Most published research comes from Northern Europe and the US, while it is accepted that both social welfare systems and societal factors vary substantially across countries. These issues haven’t been explored in Southern Europe. A better understanding of the factors associated with the level of health of single mothers in different settings is needed in order it better identify high-risk groups. Study Purpose: The aim of this study was to assess the health of single mothers in Cyprus for the first time. In particular, it aims to evaluate the level of self assessed general health, psychological burden and the presence of clinical depressive symptoms in single mothers as well as the association with demographic, social and economic characteristics. Particular emphasis is given on investigating the relation of health, with the level of perceived social support. Material and method: A descriptive-correlational study design with cross-sectional comparisons was applied. Participating mothers were selected using snowballing techniques. General health was assessed in terms of Self-Rated Health (SRH), the psychosomatic burden was evaluated using the General Health Questionnaire (GHQ-28), while the presence of clinically depressive symptoms was assessed with the Center of Epidemiological Studies – Depression Scale (CES-D). Level of social support was evaluated with Social Provision Scale (SPS). The metric properties of the scales were determined with the use of Cronbach’s internal consistency coefficients. Descriptive and inferential statistics were used in the analysis of the data. Univariable associations between study outcomes and socio-demographic characteristics were assessed in chi-square test. The level of statistical significance was set at 0.005. Multivariable stepwise logistic regression models were used, to determine the main association with socio-demographic predictors of each health outcomes. Multivariable hierarchical logistic models were used to investigate the association between health outcomes and the level of social support, before and after adjusting for the potential confounding effect of other covariates. Results: The sample consisted of 316 single mothers. The mean age of participants was 39,17 years. 41.3% of single mothers in Cyprus evaluated their level of general health as ‘less than good’ and 44.6% scored high in terms of psychosomatic burden. The prevalence of depressive symptoms (CES-D score ≥ 22) was 38.9%, which is almost three times greater than the general population. Strong associations with all health assessment tools were observed with variables relating to the presence of economic difficulties and pre-existing illness. Widows (OR = 3.3, 95% CI: 1,016-10.717), unemployed single mothers (OR = 1,268, 95% CI: 0.534-3.016) and those who do not receive financial support from the father of their children (OR = 1,759, 95% CI: 1,056-2.931) were more likely to assess their general health as worse. In contrast, single mothers aged between 35-44 years of age (OR = 3.44, 95% CI: 1.780 – 6.673), separated (OR = 4,308, 95% CI: 15.170 – 1224), who were single mothers between 1 and 2 years (OR = 2.272, 95% CI: 1,116- 4,230) and the lowest monthly family income (OR = 6.658, 95% CI: 1.612-27.495), were more likely to suffer psychosomatic burden and manifest clinically significant depressive symptoms. Social support as perceived by the mothers displayed a strong negative independent association with all tools, with mothers in the quartile with the lowest social provision scores appearing of high risk of worse general health (OR = 2,758, 95% CI :1,125 - 6,761) and psychosomatic burden (OR = 7.930, 95% CI :3,087 - 20,371), and much greater with the presence of depressive symptoms (OR = 20.523, 95% CI :7,575 - 55,523), even after adjusting confounders. Conclusions: Single mothers in Cyprus experience increased socio-economic problems which adversely affect the level of their psychosomatic health which increases the likelihood of depressive symptoms. Social support provided, appears to be particularly important, since lower levels of perceived social support provision is strongly related to their psychosomatic health. These findings can be a challenge for health care professionals, especially those working in the field of community-family nursing and highlight the necessity of interventions and strategies at community level in order to support this vulnerable population group.
Keywords: Single parent family; Single mothers; Health; Depressive symptoms; Social support; Community nursing; Μονογονεϊκή οικογένεια; Μητέρες; Υγεία; Συμπτώματα κατάθλιψης; Κοινωνική στήριξη; Κοινοτική νοσηλευτική